2010
DOI: 10.1007/s11199-010-9757-7
|View full text |Cite
|
Sign up to set email alerts
|

Violent Female Action Characters in Contemporary American Cinema

Abstract: This research is a content analysis of violent female action characters ("VFAC") shown in American action films from 1991 through 2005. The analysis focused on three aspects of VFACs: (1) gender stereotypes, (2) demographics, and (3) quantity and type of violence. Findings showed that 58.6% of VFACs were portrayed in a submissive role to the male hero in the film, and 42% were romantically linked to him. The average VFAC was young, white, highly educated, and unmarried. VFACs engaged in masculine types of viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…In fact, except for a brief dialogue with her daughter at the beginning of the film, the character played by Natalie Portman is the only female role that speaks in the entire film, and even she remains strongly defined by her role as mother, lover and housewife. This agrees with the study by Gilpatric (2010), which showed how the presence of Violent Female Action Characters (VFAC), although it could be a sign of equality, only reinforces gender stereotypes when they are submissive and defined by their romantic relationship with a man. Therefore, we can also affirm that in this film femininity is not necessarily a barrier to leading the narration, but masculinity helps to gain presence and active roles.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, except for a brief dialogue with her daughter at the beginning of the film, the character played by Natalie Portman is the only female role that speaks in the entire film, and even she remains strongly defined by her role as mother, lover and housewife. This agrees with the study by Gilpatric (2010), which showed how the presence of Violent Female Action Characters (VFAC), although it could be a sign of equality, only reinforces gender stereotypes when they are submissive and defined by their romantic relationship with a man. Therefore, we can also affirm that in this film femininity is not necessarily a barrier to leading the narration, but masculinity helps to gain presence and active roles.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, women are typically portrayed in a sexualized manner [11][12][13][14]. Despite the emergence of violent female action characters in more recent films (e.g., Lara Croft), violent portrayals in movies are overwhelmingly by male characters and/or are characterized by masculine stereotypes, such as aggressiveness [15,16]. Furthermore, although movies are a major source of youth exposure to media content [17][18][19] and are equally attended by young men and women [18], it is well documented that women are underrepresented in films (as well as other media) [12].…”
mentioning
confidence: 99%
“…Content forms include news, music videos, interactive video games, health storylines, violent entertainment, children’s entertainment, child-directed advertising, and adult-directed advertising. In six papers (Finger et al 2010 ; Gilpatric 2010 ; Mager and Helgeson 2010 ; Neuendorf et al 2010 ; Smith et al 2010 ; Welsh 2010 ), scholars compared content across as many as 50 years.…”
Section: Discussionmentioning
confidence: 99%